2017
DOI: 10.21448/ijsm.372108
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of Calendula officinalis callus extract

Abstract: The purpose of this study was to determine the antibacterial activity of C. officinalis callus derived from cotyledon explants. Cotyledons excised from in vitro germinated seedlings were used as explants. Explants were transferred on MS medium supplemented with benzil amino purine (BAP; 2 mg l -1 ), α-naphthalene-acetic acid (NAA; 2 mg l -1 ) for callus studies. The cultures were maintained on the same media compositions and were subcultured at an interval of 4 weeks. Callus cultures were harvested at the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The coloration of the calli in this study ranged from white to yellow, orange, brown, and black, and the calli were often multicolored. Similar coloration and texture were also found in calli derived from hypocotyls [11], but the calli derived from the leaves and cotyledons were in shades of green [12]. The color of calli induced from leaves and florets also depended on sucrose concentrations in medium and was light green at lower concentrations and cream-yellow at higher concentrations [34].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The coloration of the calli in this study ranged from white to yellow, orange, brown, and black, and the calli were often multicolored. Similar coloration and texture were also found in calli derived from hypocotyls [11], but the calli derived from the leaves and cotyledons were in shades of green [12]. The color of calli induced from leaves and florets also depended on sucrose concentrations in medium and was light green at lower concentrations and cream-yellow at higher concentrations [34].…”
Section: Discussionsupporting
confidence: 58%
“…The combinations 2.4-D + KIN and 2.4-D + 2iP used previously [12] induced calli with much lower efficiency. Other growth hormones have proven effective for other explants such as hypocotyls, cotyledons, cotyledon nodes [11], and floret explants [34]. Calli initiated from different types of explants of C. officinalis L. tend to be variable in their color and texture, which also changes during cultivation depending on the growth regulators used for callus initiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of employing herbs as anti-microbial agents include low toxicity, cost-effectiveness, improved patient tolerance, and the fact that they are renewable in nature (19). Cetin et al found that ethanol and chloroform extracts of C.officinalis callus inhibited Staphylococcus aureus and Bacillus cereus (20). Efstratiou et al revealed that C.officinalis showed excellent antibacterial activity against E. faecalis, E. coli, K. aerogenes, K. pneumonia, and P. aeruginosa (21).…”
Section: Anti-microbial Activitymentioning
confidence: 99%